Recent development of methanol electrooxidation catalysts for direct methanol fuel cell - Gong, Liyuan; Yang, Zhiyuan; Li, Kui; Xing, Wei; Liu, Changpeng; Ge, Junjie (Journal of energy chemistry, 2018)
Direct methanol fuel cells (DMFCs) are very promising power source for stationary and portable miniature electric appliances due to its high efficiency and low emissions of pollutants. As the key material, catalysts for both cathode and anode face several problems which hinder the commercialization of DMFCs. In this review, we mainly focus on anode catalysts of DMFCs. The process and mechanism of methanol electrooxidation on Pt and Pt-based catalysts in acidic medium have been introduced. The influences of size effect and morphology on electrocatalytic activity are discussed though whether there is a size effect in MOR catalyst is under debate. Besides, the non Pt catalysts are also listed to emphasize though Pt is still deemed as the indispensable element in anode catalyst of DMFCs in acidic medium. Different catalyst systems are compared to illustrate the level of research at present. Some debates need to be verified with experimental evidences. Methanol eletrooxidation mechanism, anode catalyst preparation method and category, application of catalyst in fuel cell, and DMFCs opportunities and challenges are discussed in this review. [Display omitted]